Frontispiece: Sulfates‐Based Nanothermites: An Expanding Horizon for Metastable Interstitial Composites. Issue 15 (7th April 2015) - Comet, Marc; Vidick, Geoffrey; Schnell, Fabien; Suma, Yves; Baps, Bernard; Spitzer, Denis
<x xml:space="preserve">Abstract</x> Metastable Materials D. Spitzer et al. report in their Communication on page 4458 ff. the preparation of energetic nanothermites from metal sulfates and aluminum nanopowder. These new materials are characterized by fast combustion velocities and extremely low sensitivity to friction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>